Psychometric Properties of Older Adults’ Entomophobia and Arachnophobia Scale (OAEAS): Validating, Cutoff Points, IRT Analysis, and Its Measurement Invariance in Iranian Version - Mahsa Nasrabadi; Seyyed Mansour Kashfi; Aboozar Soltani; Siti Anom Binti Ahmad; Abdolrahim Asadollahi (Psyche: A Journal of Entomology)
Discussion: The new version of OAEAS 18-items is a valid and reliable tool for assessing fear of insects or other arthropods in Iranian community-dwelling older adults. The possible uses and limitations of the Iranian version of the scale were also discussed.